2022
DOI: 10.1101/2022.12.20.521169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic load and adaptive potential of a recovered avian species that narrowly avoided extinction

Abstract: High genetic diversity is often a good predictor of long-term population viability, yet some species persevere despite having low genetic diversity. Here we study the genomic erosion of the Seychelles paradise flycatcher (Terpsiphone corvina), a species that narrowly avoided extinction after having declined to 28 individuals in the 1960s. The species recovered unassisted to over 250 individuals in the 1990s and was downlisted from Critically Endangered to Vulnerable in the IUCN Red List in 2020. By comparing h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…In other words, our proxy‐based assessment, which was completed in less than one year, obtained more estimates of Ne than a decade of hundreds of DNA‐based studies. We acknowledge that Ne quantified using genetic data may, in some cases, be more accurate than that estimated using proxy data, and that genetic data is crucial for assessing the effect of genomic erosion (e.g., Femerling et al., 2023). However, using proxies, we have shown that estimates of Ne can be obtained in a rapid and efficient manner, which can enable the tracking and reporting of genetic information on large scales in all countries.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, our proxy‐based assessment, which was completed in less than one year, obtained more estimates of Ne than a decade of hundreds of DNA‐based studies. We acknowledge that Ne quantified using genetic data may, in some cases, be more accurate than that estimated using proxy data, and that genetic data is crucial for assessing the effect of genomic erosion (e.g., Femerling et al., 2023). However, using proxies, we have shown that estimates of Ne can be obtained in a rapid and efficient manner, which can enable the tracking and reporting of genetic information on large scales in all countries.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we complemented our Vortex analyses with computer simulations in SLiM (Haller & Messer, 2019). Like Vortex, this forward‐in‐time, individual‐based‐model enabled us to simulate the impacts of conservation action on population viability many generations into the future (Bertorelle et al., 2022; Femerling et al., 2023; Jackson et al., 2022). Using SLiM, we were also able to simulate the ancestral population size, rates of decline, and contemporary population sizes based on the known demographic history of the Arabian leopard (Al Hikmani et al., 2023).…”
Section: Methodsmentioning
confidence: 99%
“…This is expected, as genetic diversity loss has a time-lag relative to demographic decline, particularly in long-lived species 47 . Genetic diversity loss in collapsed populations (e.g., Svalbard) is expected to continue even if there is demographic recovery 48,49 , because small populations continue to pay a ‘genetic drift debt’ 50 . This sustained genomic erosion, especially in the ‘East Greenland Svalbard Barents Sea’ stock, brings into question the long-term resilience of the population.…”
Section: Main Textmentioning
confidence: 99%